Effect of Oxidized Fibrinogen on Hemostatic System: In Vitro Study - TETİK, ŞERMİN (SAGE PUBLICATIONS INC, 2011)
Standard coagulation assays were performed with control and oxidized fibrinogen (Fg), using prothrombin time (PT; 12.5 +/- 0.4 vs 25 +/- 0.8 seconds, P < .001) and activated partial thromboplastin time (aPTT; 33 +/- 2.5 vs 63 +/- 4.7 seconds, P < .001). Fibrin clot (MA), clot formation initiation (r), and rate of clot lysis (LY30) were measured, a reflection exposure of Fg to Fe(3+)/ascorbate oxidative system by thrombelastograph (TEG) analysis (0, 6, 12, 24, and 48 hours, 6.2 +/- 1.3 vs 5.5 +/- 1.2, 4.3 +/- 1.0 [P < .01], 3.9 +/- 1.6, 3.2 +/- 0.8, [P < .001]). Maximum amplitude level was found to be lower than control (69.1 +/- 7.2 vs 67.9 +/- 12.4, 64.0 +/- 11.4, 60.2 +/- 21.2, 42.2 +/- 15.2, P < .001). The lysis rate was changed according to oxidation time between Fg exposed to Fe(3+)/ascorbate and control exposed to Fe(3+)/ascorbate for the same treatment time (1.9 +/- 0.71 vs 7 +/- 0.5, 1.6 +/- 0.1, 1.2 +/- 0.5, 0.9 +/- 1.3, P < .001). We revealed dysregulation of hemostatic system with contribution of oxidized Fg, which was in direct proportion to the intensity of Fg oxidation.
Keywords: oxidized fibrinogen; thrombelastography; hemostasis; FLOW-CYTOMETRIC METHOD; OXIDATIVE MODIFICATION; AMINO-ACIDS; CATALYZED OXIDATION; CLOT FORMATION; O-TYROSINE; PROTEIN; DITYROSINE; ATHEROSCLEROSIS; IIB/IIIA